Ecotourism impacts in Pulau Kukup National Park: Exploring resident perspectives / Ahmad Edwin Mohamed ... [et al.] - Mohamed, Ahmad Edwin; Alwi, Mohamad Khairi; Xing, Lim Wen (Faculty of Hotel and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2020)
Studies on resident perceptions toward the impacts of tourism development provide crucial feedbacks and information to the local tourism authorities. This study, in particular, investigatedthe effects of eco- tourism activities from environmental, economic, and social perspectives using social exchange theory as the theoretical foundation. A total of 200 questionnaires were distributed to the local residents who live in Kukup, a small fishing town adjacent to Pulau Kukup National Park to assess their views on the above aspects. The sampling procedure employed was a systematic random sampling of every 5th house in Kukup with a random starting point. The results of the descriptive analysis indicated that the residents, in general, perceived the environmental, economic, and social impacts in both positive and negative manners. However, residents tend to score higher on the positive aspects than the negative aspects of all three dimensionsof impacts. In particular, residents rated the economic impacts verypositively than environmental and social impacts. Besides the above, the ANOVA and t-test analyses also suggest that the resident perceptions varied significantly according to age, education, occupation, and income.